The drivers of influenza vaccination in adults: Insights from a national Australian survey - Maria Christou-Ergos; Majdi M. Sabahelzain; Maryke Steffens; Jessica Kaufman; Katarzyna T. Bolsewicz; Margie Danchin; Julie Leask (Vaccine: X, 2025)
Influenza vaccination coverage is suboptimal in the Australian adult population. While coverage data is used to monitor uptake, at present, there is no systematic data collection on the behavioural and social drivers of vaccination. This study used a globally standardized survey tool to measure constructs related to influenza vaccination within four domains (i) vaccination-related thoughts and feelings, (ii) social processes, (iii) motivation, and (iv) practical issues.An online survey was administered to a sample of 2055 Australian adults recruited via an online panel in March 2024. Logistic regression analysis was used to determine factors that contributed to people's intention to receive an influenza vaccine.Most Australian adults (62.8 %) wanted an influenza vaccine in the upcoming influenza season. The odds of wanting an influenza vaccine were significantly greater for people who: had received an influenza vaccine in the preceding two years (aOR:10.35; 95 % CI: 7.09–15.11) p < .001; thought the influenza vaccine offered personal protection (aOR:2.66; 95 % CI: 1.76–4.01) p < .001; thought the influenza vaccine offered protection to others (aOR:1.6; 95 % CI: 1.08–2.39) p = .02; thought the influenza vaccine was important for their own health (aOR:1.53; 95 % CI: 1.03–2.27) p = .04; felt a social responsibility to get an influenza vaccine (aOR:4.05; 95 % CI: 2.88–5.68) p < .001; believed close family and friends wanted them to get the influenza vaccine (aOR:2.35; 95 % CI: 1.67–3.3) p < .001; believed community leaders wanted them to get the influenza vaccine (aOR:1.48; 95 % CI: 1.08–2.01) p = .01; received a recommendation to get the influenza vaccine from a health care worker in last two years (aOR:1.7; 95 % CI: 1.24–2.32) p < .001.This study provides a foundation for ongoing national monitoring of the drivers of influenza vaccination. This will help tailor timely strategies to population needs. Strategies that increase confidence in the value of vaccination, foster positive social norms within communities and increase access to vaccine services may help increase influenza vaccine acceptance.